The Passivation Behavior of Sputter-Deposited W-Ti Alloys in 1 M NaOH Solution - Sharmah, A.; Jha, H.; Bhattarai, J. (Journal of Nepal Chemical Society, 2007)
The passivation behavior of the sputter-deposited amorphous or nanocrystalline W-Ti alloys is studied in alkaline 1 M NaOH solution at 25oC, open to air using corrosion tests, electrochemical measurements and confocal scanning laser microscopic (CSLM) techniques. The corrosion rates of the W-Ti alloys decreased with increasing titanium content and the corrosion rates of the alloys containing 53 at % (atomic percentage) or more titanium as well as the sputter-deposited titanium metal are nearly two orders of magnitude lower than that of the sputter-deposited tungsten in 1 M NaOH solution. The pitting corrosion is clearly observed in the W-Ti alloys containing 30-53 at % titanium from CSLM studies. The open circuit potentials of all the examined W-Ti alloys are located between those of tungsten and titanium metals. DOI: 10.3126/jncs.v22i0.518 Journal of Nepal Chemical Society Vol. 22, 2007 pp.17-25